IPF, comorbidities and management implications - Vancheri, Carlo; Cottin, Vincent; Kreuter, Michael; Hilberg, Ole (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Idiopathic pulmonary fibrosis (IPF) is a complex disease that is associated with various respiratory and non-respiratory comorbidities. The most common comorbidity is cardiovascular disease (CVD), which increases in incidence with increasing duration of IPF and is associated with a higher risk of mortality. The direction of causality between CVD and IPF is unclear. There is evidence that IPF is associated with a prothrombotic state; however, warfarin is not beneficial in IPF patients. Lung cancer is another common comorbidity, being present in more than 50% of IPF patients at 10 years after diagnosis. IPF and lung cancer share several risk factors and pathogenic pathways and also show a similar anatomic distribution; this can make radiological diagnosis difficult. As with CVD, lung cancer in IPF patients is associated with a significantly worse prognosis and treatment options are limited. Surgery, chemotherapy, and radiotherapy have all been associated with an increased risk of morbidity and mortality. However, treatment may be considered in selected patients with less advanced cancer and less advanced IPF. Emphysema may occur in patients with IPF and is believed to represent a distinct clinical syndrome, known as the combined pulmonary fibrosis and emphysema (CPFE) syndrome. CPFE has a strong male predominance, is strongly linked with smoking, and has distinct radiographic features. CPFE is also associated with a very high frequency of pulmonary hypertension, which is associated with a poor prognosis. There are no specific treatments for CPFE and evaluation of IPF therapies in CPFE patients is urgently needed. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32; Suppl 1: 17-23)